2017
DOI: 10.21608/jvmr.2017.43264
|View full text |Cite
|
Sign up to set email alerts
|

Organochlorine pesticides residues in butter, olive oils and corn oils

Abstract: Dietary fat and oil is important for many body processes. The present investigation was carried out to determine the concentrations of organochlorine pesticides in butter, olive and corn oil. A total of 125 samples (75 butter, 25 each of olive oil and corn oil) were collected from El Minia Governorate, Egypt. Levels of these compounds were determined by gas chromatography with electron capture detector (GC-ECD). The results indicated that 30.4%(38/125), 24.8%(31/125), 21.6%(27/125), 21.6%(27/125), 16.8%(21/125… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 27 publications
0
0
0
Order By: Relevance
“…By comparing the concentrations of 4,4-DDE that we obtained in the present work with the levels recorded in previous studies in other countries, we found that there was a clear difference, and that the levels of 4,4-DDE that were recorded in Jordan were significantly higher than those recorded in Croatia (0.44 µg/kg; Romanić et al, 2011), Spain (1.8 µg/kg; Yagüe et al, 2005), and Italy (0.59 µg/kg; Guerranti et al, 2008); and not detected in Egypt (El-Shinawy et al, 2017). On the other hand, other compounds of the OCPs were detected in the samples of those countries that were not found in the Jordanian olive oil samples.…”
Section: Level Of Ocps and Risk Assessmentsupporting
confidence: 51%
See 2 more Smart Citations
“…By comparing the concentrations of 4,4-DDE that we obtained in the present work with the levels recorded in previous studies in other countries, we found that there was a clear difference, and that the levels of 4,4-DDE that were recorded in Jordan were significantly higher than those recorded in Croatia (0.44 µg/kg; Romanić et al, 2011), Spain (1.8 µg/kg; Yagüe et al, 2005), and Italy (0.59 µg/kg; Guerranti et al, 2008); and not detected in Egypt (El-Shinawy et al, 2017). On the other hand, other compounds of the OCPs were detected in the samples of those countries that were not found in the Jordanian olive oil samples.…”
Section: Level Of Ocps and Risk Assessmentsupporting
confidence: 51%
“…Cui et al (2020) reported EDI value of 0.000656 µg/kg/day for 11 OCPs in olive oil samples purchased from local markets in China with HRI value less than 1, thus also indicating low human health risk. In Egypt, researchers reported EDI value of 0.000006 µg/kg/day for 14 OCPs in olive oil samples from El Minia governorate (El-Shinawy et al, 2017). Among the 16EPA PAHs that we studied, eight congeners were detected in the analysed samples namely Nap, Fl, Phe, Ant, Flu, Pyr, BaA, and Chr.…”
Section: Level Of Ocps and Risk Assessmentmentioning
confidence: 75%
See 1 more Smart Citation